METODE PEMBINAAN KEAGAMAAN DALAM MEMBENTUK KARAKTER ISLAMI PADA ANAK BINAAN DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS II JAKARTA - Anisa Anggraeni; Busahdiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of religious guidance in shaping adoles-cents’ character, particularly for fostered children at the Special Development Insti-tution for Children (LPKA) Class II Jakarta. The limited environment within the insti-tution often creates psychological pressures such as stress, boredom, and low self-esteem. Therefore, religious guidance is needed to instill Islamic values, improve behavior, and develop Islamic character so that fostered children are better pre-pared to return to society. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation related to the imple-mentation of religious guidance activities at LPKA Class II Jakarta. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The results show that religious guidance is implemented through congregational prayers, Qur’an recitation, religious studies, and lectures using dialogic approaches, role modeling, habituation, and worship practices. These programs positively influ-ence behavioral changes among fostered children, including increased religious awareness, discipline, and motivation to improve themselves.